Artemisias: Works of Artemisia Gentileschi - Pinto, Elaine Carolina (2021)
Aiming to understand the historical figure of Artemisia Gentileschi (1593-1653), based on studies of the life and work of the Italian painter, this article analyzes the construction of the image of Artemisia by herself, having as object her work Self-portrait as the allegory of Painting (1638-1639). Furthermore, the construction of the character Artemisia, by Susan Vreeland (2010), in The passion of Artemisia (2010), a novel that became a supplement to the artist’s story and can be interpreted based on studies on intermediality, analyzing the relationship between image and text.